2009
DOI: 10.1038/labinvest.2009.80
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin attenuation of dextran sulfate sodium-induced colitis in mice

Abstract: Osteopontin (OPN) is a matricellular cytokine present in most tissues and body fluids; it is known to modulate immune responses. In previous studies using the dextran sulfate sodium (DSS) acute colitis model, we found exacerbated tissue destruction and reduced repair in OPN-null (À/À) mice compared with wild-type (WT) controls. As OPN is normally present in milk, we hypothesized that administration of OPN may protect the intestines from the adverse effects of experimental colitis. A volume of 20 or 2 mg/ml bov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 62 publications
6
49
0
1
Order By: Relevance
“…However, studies addressing the role of Opn during DSS-induced colitis, another chemically induced model, have been contradictory (14,15,(60)(61)(62)(63). Opn deficiency in Black Swiss mice was protective (15), whereas Opn deficiency in C57BL/6 mice resulted in increased intestinal tissue destruction (60) (61) found that Opn was anti-inflammatory during acute DSS colitis but proinflammatory during chronic DSS colitis.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies addressing the role of Opn during DSS-induced colitis, another chemically induced model, have been contradictory (14,15,(60)(61)(62)(63). Opn deficiency in Black Swiss mice was protective (15), whereas Opn deficiency in C57BL/6 mice resulted in increased intestinal tissue destruction (60) (61) found that Opn was anti-inflammatory during acute DSS colitis but proinflammatory during chronic DSS colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent attempts to define a role for OPN in intestinal inflammation, using a chemically induced model of colitis (DSS), have yielded conflicting results. While our group has shown that OPN Ϫ/Ϫ mice are more susceptible to DSS colitis, through a reduction in tumor necrosis factor-␣ and neutrophil recruitment, 10,12 other investigators found an opposite effect. 9 More recently, Heilmann et al 11 found that OPN Ϫ/Ϫ mice are more susceptible to acute challenge with DSS, associated with reduced IL-22 and macrophage activity but increased serum tumor necrosis factor-␣, while chronic DSS-induced colitis was reduced in these mice.…”
Section: Discussionmentioning
confidence: 57%
“…In contrast, addition of topical OPN through rectal administration in OPN Ϫ/Ϫ mice did restore effects of C. rodentium infection, possibly because OPN may be differentially processed and internalized in the in vivo setting. The ability of exogenous OPN to be absorbed and attenuate DSS-induced colitis 12 supports a potential use for this compound in future research.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It has been demonstrated that serum OPN level is elevated in IBD patients and correlates with disease activity [87][88][89][90][91]. However, some studies in humans and in animal models of colitis gave opposite results, suggesting a dual or protective function of OPN in intestinal inlammation [86,[91][92][93][94][95][96][97][98][99].…”
Section: Inlammatory Bowel Diseasesmentioning
confidence: 99%